Relationship between sport commitment and sport consumer behavior - Fernandes, Norberta Elisa (2013)
The purpose of this study was to examine the relationships between sport commitment and three types of sport consumer behaviors: participation frequency, sporting goods and media consumption. A survey was conducted among sport participants of both individual and team sports, fitness and outdoor activities (n= 900). The survey included questions related to demographic information, measures of sport commitment and sport consumption behavior. The results analyzed trough structural equation modeling showed that the sport commitment influences positively the participation frequency, sporting goods consumption and media consumption. Implications of these results are discussed and suggestions for future research on sport consumers are provided.